2003
DOI: 10.1097/00006676-200305000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Local Growth Factors Are Beneficial for the Autonomic Reinnervation of Transplanted Islets in Rats

Abstract: Local growth factor treatment has a beneficial effect on autonomic reinnervation as well as islet integrity and survival of the graft after islet transplantation in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Similarly, studies in pigs have shown that the vascularization and reinnervation of skin grafts are coordinated (5). It is likely that growth factors are involved in the coordinated reinnervation and vascularization of transplants (30,31) and may contribute to innervation of the ectopic endometrial growths. Thus, of relevance to ENDO in women, Anaf et al (7) found that nerve growth factor expression was greater in deeply infiltrating adenomyotic endometrial nodules when compared with other ectopic endometrial growths and that these nodules were located closer to nerve fibers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, studies in pigs have shown that the vascularization and reinnervation of skin grafts are coordinated (5). It is likely that growth factors are involved in the coordinated reinnervation and vascularization of transplants (30,31) and may contribute to innervation of the ectopic endometrial growths. Thus, of relevance to ENDO in women, Anaf et al (7) found that nerve growth factor expression was greater in deeply infiltrating adenomyotic endometrial nodules when compared with other ectopic endometrial growths and that these nodules were located closer to nerve fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of transplanted tissues indicate that their reinnervation, particularly by sympathetic fibers, can be important not only for better functioning of transplanted tissues but also their survival (5,31,39,40). Furthermore, the fact that the sensory fibers expressing SP and CGRP are anatomically intimate with the vasculature of the cyst wall and extend terminals among the epithelial cells lining the cyst lumen suggests they have both sensory and efferent functions.…”
Section: Discussionmentioning
confidence: 99%
“…When islets and NCSCs were co-cultured in the upper compartment, no beta cells proliferated in the lower compartment that contained islets only (n03-4, p>0.1 for all comparisons). White bars indicate an empty insert, hatched bars an insert containing NCSCs and black bars, an insert containing a coculture of islets and NCSCs mice [4,38]. Interestingly, not only beta cells but also nerve structures seem to be affected by the autoimmune assault seen during type 1 diabetes, and nerves disappear before any loss of beta cells occurs in type 1 diabetic BB rats [5,6], which may hamper beta cell regenerative capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Ngfb promotes b-cell survival 33,34 and increases islet morphogenesis. 35 RT-PCR analysis revealed lower Ngfb expression in BBdp rats (Figure 6d), which could further contribute to the reduced capacity for b-cell survival and islet expansion.…”
Section: Decreased Ngfb and Pdx1 Gene Expressionmentioning
confidence: 99%